2000
DOI: 10.1117/12.382840
|View full text |Cite
|
Sign up to set email alerts
|

<title>White-light-emitting diodes for illumination</title>

Abstract: White light for illumination can be produced from LEDs either by combining red, green and blue emitting chips in one lamp, or by using phosphors to down-convert the emission of short wavelength emitting InGaN LEDs. Both concepts will be critically reviewed, and simulations compared with experimental evaluations. As expected, each solution has advantages, but also drawbacks, which are weighted by the specifics ofthe applications. The overall picture strongly depends on the efficiencies of the single color chips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(45 citation statements)
references
References 1 publication
0
45
0
Order By: Relevance
“…High temperature levels can degrade the optical performance of the encapsulation and the lens. [1][2][3][4] It has been already shown that thermal stress degrades the luminous output of the devices. [15][16][17][18][19][20][21][22][23] This study aims at studying the effect of blue light intensity together with thermal stress on the lumen depreciation and the reliability of LED-based products and on the acceleration of optical degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High temperature levels can degrade the optical performance of the encapsulation and the lens. [1][2][3][4] It has been already shown that thermal stress degrades the luminous output of the devices. [15][16][17][18][19][20][21][22][23] This study aims at studying the effect of blue light intensity together with thermal stress on the lumen depreciation and the reliability of LED-based products and on the acceleration of optical degradation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In this type of LED, the phosphor is either coated on the chip or mixed with the lens disc. [11][12][13][14][15][16][17][18][19][20][21][22] The spatial distribution of phosphor in white LED lamps strongly influences the colour uniformity and the efficiency of the light source.…”
Section: Introductionmentioning
confidence: 99%
“…1 2+ (x = 0) exhibited blue emission with a peak maximum at 470 nm under excitation at 320450 nm, which was quite consistent with a previous report by Jia et al 19) On the other hand, the Sr-substituted samples with x = 0.250.75 showed broad red emission around 630 nm when they were excited at 300450 nm. The blue emission at 470 nm, which was characteristic of Ca 4 -substitution facilitated by the Srsubstitution would be one possible mechanism to explain the appearance of new emission band. 22) There are four different Casites in the crystal structure of Ca 4 Si 2 O 7 F 2 , as shown in Fig.…”
Section: +mentioning
confidence: 99%
“…Numerous investigations have been performed on various parts of LED-based products; however, not much has been done on the lens/remote phosphors of the LEDs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Recent reliability studies [14][15][16][17][18][19] have shown that the optical degradation of white LED products is mainly due to the aging of the encapsulants/lens. The encapsulants/lens are mainly used to prevent thermal shock and mechanical stress as well as humidity-induced corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are different technologies used to produce white light high-power LED systems. [4][5][6][7][8] The most common one is combining a blue chip with yellow phosphor. In such a system, the phosphor layer can be either deposited directly on the chip or incorporated into a lens disk.…”
Section: Introductionmentioning
confidence: 99%